HCM Farma As An Innovative Pharmacy Model: Digitalization Strategy To Increase Local Competitiveness - Wijaya, Raindra Saptono; Soleh , Ahmad; Effendi , Bahman (Universitas Dehasen Bengkulu, 2025)
Digitalization has become a key element in the transformation of the pharmaceutical sector, providing opportunities to improve operational efficiency, expand service access, and introduce new innovations. HCM Farma, a local pharmacy in Indonesia, has adopted a digitalization strategy by leveraging technologies such as cloud computing, mobile applications for telepharmacy services, and digital health education systems. This study aims to analyze the implementation of digitalization at HCM Farma as an innovative pharmacy model to enhance local competitiveness. Through a literature review approach, the study found that the application of cloud computing enables real-time drug inventory management, thereby improving operational efficiency and accuracy. The telepharmacy service available through the mobile app expands healthcare accessibility, especially for patients in remote areas. Additionally, the digital health education feature helps patients better understand medication use, increasing their involvement in health management. However, the implementation of this digitalization strategy faces challenges such as high investment costs and patient data security issues. To address these challenges, it is recommended to strengthen collaboration with technology providers, provide continuous staff training, and enhance data security systems. The results of this study show that digitalization in the pharmaceutical sector, when applied correctly, can provide a competitive advantage for local pharmacies like HCM Farma. Furthermore, digitalization also contributes to improving healthcare access and quality in Indonesia, particularly in hard-to-reach areas.